2018
DOI: 10.1371/journal.pone.0199659
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of myeloperoxidase-anti-neutrophil cytoplasmic antibody in idiopathic interstitial pneumonias

Abstract: ObjectiveAlthough a possible association among myeloperoxidase-anti-neutrophil cytoplasmic antibody (MPO-ANCA), microscopic polyangiitis (MPA), and idiopathic pulmonary fibrosis (IPF) has been suggested, the clinical significance of MPO-ANCA in idiopathic interstitial pneumonias (IIPs), including IPF and non-IPF, remains unclear. We aimed to investigate the frequency of MPO-ANCA positivity, as well as MPA incidence and risk factors for development in patients initially diagnosed with IIP.MethodsWe retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 21 publications
(34 reference statements)
3
44
2
Order By: Relevance
“…Interstitial lung disease (ILD) is increasingly observed in association with MPO-ANCA antibodies with or without other manifestations of AAV 139140141. Whereas treatment of ILD in patients with other AAV manifestations follows the typical approaches described earlier, the management of ILD and a positive ANCA test without other AAV manifestations is uncertain.…”
Section: Treatment Challenges Associated With Specific Manifestationsmentioning
confidence: 99%
“…Interstitial lung disease (ILD) is increasingly observed in association with MPO-ANCA antibodies with or without other manifestations of AAV 139140141. Whereas treatment of ILD in patients with other AAV manifestations follows the typical approaches described earlier, the management of ILD and a positive ANCA test without other AAV manifestations is uncertain.…”
Section: Treatment Challenges Associated With Specific Manifestationsmentioning
confidence: 99%
“…The association of IP and ANCA does not seem to be fortuitous . Hironao Hozumi et al found that MPO‐ANCA positivity was associated with subsequent MPA development in patients initially diagnosed with IIP, especially those with UIP pattern on HRCT. If patients with IP are found to have positive MPO‐ANCA, there may be two possibilities, on the one hand, MPO‐ANCA may play a part in the development of IP, on the other hand, fibrotic process may induce production of the MPO‐ANCA .…”
Section: Discussionmentioning
confidence: 99%
“…The first assumption is that MPO may play a role in pulmonary fibrosis and the second that pulmonary fibrosis may induce the production of the antibody. [9][10][11] Extra pulmonary manifestations in IPF requires ANCA testing in order to rule out the possibility of a co-existing vasculitis. IPF with positive anti-MPO antibodies is associated with the risk of MPA development and certainly worst prognosis.…”
Section: Discussionmentioning
confidence: 99%